ANALYSIS OF POWER RELATION AND MUSIC IN THE EXISTENCE OF ‘SLANK’ (FOUCAULT’S CRITICAL DISCOURSE) - Rully Rully; Andi Mirza Ronda; Mikhael Dua (Bajang Institute, 2023)
Slank is a phenomenal Indonesian band that exists today. Its existence in the music industry for more than three decades has given its style to Indonesian music, consistent with the criticisms that represent the voices of some people who are dominant at the bottom or are intimidated. The neatly fragmented social dynamics in each Slank album are like historiography in the form of music. With the postmodernism paradigm and the Poststructuralist approach a la Foucault, this article will examine the relations of power and music in the existence of Slank. Thus finding that 'criticism' is a form of Slank's continuation with its 'exotic' style representing Indonesia which has a lot of cultural blends that always appear arbitrary as a Slank identity to become an aesthetic existence a la Slank, which is a slice of meeting social issues with music that stretches wide